2018
DOI: 10.1111/jgs.15332
|View full text |Cite
|
Sign up to set email alerts
|

Opioid Prescriptions in Older Medicare Beneficiaries After the 2014 Federal Rescheduling of Hydrocodone Products

Abstract: OBJECTIVES To examine how an October 2014 Drug Enforcement Administration policy reclassified hydrocodone product from schedule III to II has affected older adults, who are among the largest consumers of prescription opioids in the United States. DESIGN Retrospective cohort study. SETTING United States. PARTICIPANTS A 20% sample of Medicare Part D beneficiaries aged 65 and older from 2013 through 2015 (> 2,500,000 beneficiaries each year) MEASUREMENTS From January 2013 to December 2015, we calculated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
36
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 39 publications
5
36
2
Order By: Relevance
“…Prior to cancer diagnosis, the prolonged opioid therapy rate for individuals diagnosed in 2008 was 7.1%, but this rate rose to 9.8% within a year of cancer treatments and to 13.3% at 5 years postcancer diagnosis. The 12.8% rate of long‐term opioid therapy of all cancer survivors in 2013 in our study is slightly lower than the 13.6% rate previously reported in the general Medicare population in Texas . However, the rates in our study varied by cancer sites, from the highest rate of 19.4% in lung cancer (a cancer requiring surgery for the early stage) to the lowest rate of 9.6% in prostate cancer (a cancer requiring minimally invasive therapies for the early stage).…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…Prior to cancer diagnosis, the prolonged opioid therapy rate for individuals diagnosed in 2008 was 7.1%, but this rate rose to 9.8% within a year of cancer treatments and to 13.3% at 5 years postcancer diagnosis. The 12.8% rate of long‐term opioid therapy of all cancer survivors in 2013 in our study is slightly lower than the 13.6% rate previously reported in the general Medicare population in Texas . However, the rates in our study varied by cancer sites, from the highest rate of 19.4% in lung cancer (a cancer requiring surgery for the early stage) to the lowest rate of 9.6% in prostate cancer (a cancer requiring minimally invasive therapies for the early stage).…”
Section: Discussioncontrasting
confidence: 77%
“…The 12.8% rate of long-term opioid therapy of all cancer survivors in 2013 in our study is slightly lower than the 13.6% rate previously reported in the general Medicare population in Texas. 30 However, the rates in our study varied by cancer sites, from the highest rate of 19.4% in lung cancer (a cancer requiring surgery for the early stage) to the lowest rate of 9.6% in prostate cancer (a cancer requiring minimally invasive therapies for the early stage). On the other hand, among the subcohort of opioid-naïve survivors, we found rates of 1.4% to 7.1%, which were substantially lower than the 10.4% rate reported by Lee et al 20 in opioid-naïve cancer patients following curative-intent surgery.…”
Section: Discussionmentioning
confidence: 64%
“…We observed that approximately one in every three Medicare beneficiaries received prescriptions for opioids during our observation period. Although not directly comparable, researchers from the Office of the Inspector General recently reported that one in three Medicare beneficiaries enrolled in the Part D program were prescribed an opioid [40] ; other researchers using Part D data found that 21.9% of Medicare beneficiaries used strong opioids in 2013 [41] . It is important to note that these studies focused on elderly Medicare beneficiaries with Part D insurance and were not specific to those with pain conditions.…”
Section: Discussionmentioning
confidence: 99%
“…These are only at the quarter level, but represent an important specific payor, that includes tramadol (along with all other opioids). Although prior work found modest decreases in rates of HCP use in the elderly following the up-scheduling of HCPs (Kuo et al, 2018), the public use version of the CMS Medicare part D data is only annual and thus we do not use Medicare data for our study.…”
Section: Background and Conceptual Frameworkmentioning
confidence: 99%